Efficient simulation of nonuniform transmission lines using integrated congruence transform. - Gad, E.
This paper presents a new algorithm based on integrated congruence transform for efficient simulation of nonuniform transmission lines. The proposed algorithm introduces the concept of model-order reduction (MOR) via implicit usage of the Hilbert-space moments in distributed networks. The key idea in the proposed algorithm is the development of an orthogonalization procedure that does not require the explicit computation of the Hilbert-space moments in order to find their spanning orthogonal basis. The proposed orthogonalization procedure can thus be used to compute an orthogonal basis for any set of elements that are related through a differential operator in a generalized Hilbert space, without the need to have these elements in an explicit form. The proposed algorithm also addresses the problem of MOR of nonuniform transmission lines, through defining a weighted inner product and norm mappings over the Hilbert space of the moments. Numerical examples demonstrate more accurate numerical approximation capabilities over using the moments explicitly.
Keywords: Hilbert space moments; RLC circuits; Differential operator; Distributed networks; Generalized Hilbert space; Integrated congruence transform; Lumped parameter networks; Model order reduction; Nonuniform transmission lines; Numerical approximation; Orthogonal basis; Orthogonalization procedure